Konsep Bermukim Kembali Pasca Relokasi: Studi Kasus Bantaran Sungai Inggoi, Desa Amasing Kota Barat - Abusama, Nikmah (Jurnal Wilayah dan Kota, 2025)
The settlement patterns of communities are often influenced by the physical conditions of their environment. The settlement along the Inggoi River banks in the Amasing area, established in 1915, became increasingly dense over time. In late 2010, the Amasing area experienced severe flooding due to continuous heavy rainfall and high tides, leading to extensive damage to most of the settlements. In response, the government implemented a relocation policy for affected residents and undertook disaster site reorganization, as the area was classified as disaster-prone. However, some relocated residents chose to return to their original settlement over a three-year period. This study employed a qualitative inductive method with a descriptive analytical approach to identify key themes and develop conceptual frameworks. Data were collected through observations and in-depth interviews with residents who returned to the Inggoi River banks and coastal areas in Desa Amasing, Kota Barat, complemented by secondary data from government agencies and traditional leaders. The findings revealed the emergence of five key concepts: (1) strong social influences rooted in customs and culture, (2) significant local economic factors, (3) residents' understanding of and coexistence with disaster risks, (4) disaster management and relocation dynamics, and (5) the ineffectiveness of government programs. Collectively, these concepts shaped the phenomenon of post-relocation resettlement along the Inggoi River in Desa Amasing Village, Kota Barat.